PPO.42 Interpreting the antenatal detection of short long bones. (9th June 2014) - Perry, PD; Budd, JLS; Draper, ES
Abstract : Objective: To establish the predictive value of an antenatal detection of 'short long bones' (SLBs) and/or IUGR in the diagnosis of skeletal dysplasia. Background: The implications of SLBs remains unclear with only 51% (116/227) notifications of SLBs reported to the East Midlands and South Yorkshire Congenital Anomalies Register (EMSYCAR) between 2008–2012 exhibiting a limb reduction deformity at delivery. Conversely, over the same period, 360 cases delivered with a limb reduction deformity, or skeletal dysplasia/syndrome, which had not been reported antenatally with either SLBs or IUGR (birth prevalence 9.6/10, 000). Methods: Each of these 360 cases was individually reviewed. Those with completely missing limbs and digits, or congenital constriction bands, for which an antenatal diagnosis of SLBs is largely inappropriate, were excluded; 211 cases remained (birth prevalence 5.6/10, 000). Results: Of 211 cases; 50/211 (23.7%) were syndromic, associated either with short stature or more general limb dysplasia; 98 (46.4%) involved an upper or lower limb reduction deformity, 28 (13.2%) had more than one reduction anomaly. 33 (15.6%) exhibited lethal skeletal dysplasia, 25 (11.8%) non-lethal unspecified dysplasias and 15 (7.1%) various forms of osteogenesis. Over half; 56.9% (120) were liveborn, 36% (76) resulted in TOP. Conclusions: While half of the cases notified antenatally with SLBs had a LRD at delivery, only a third of the total LRD cases were identified in this way. The remainder were correctly identified as skeletal dysplasias or LRDs from the earliest scan, suggesting that a description of SLBs has limited value as a soft marker.